2015
DOI: 10.1093/nar/gkv522
|View full text |Cite
|
Sign up to set email alerts
|

SLX4 contributes to telomere preservation and regulated processing of telomeric joint molecule intermediates

Abstract: SLX4 assembles a toolkit of endonucleases SLX1, MUS81 and XPF, which is recruited to telomeres via direct interaction of SLX4 with TRF2. Telomeres present an inherent obstacle for DNA replication and repair due to their high propensity to form branched DNA intermediates. Here we provide novel insight into the mechanism and regulation of the SLX4 complex in telomere preservation. SLX4 associates with telomeres throughout the cell cycle, peaking in late S phase and under genotoxic stress. Disruption of SLX4's in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 49 publications
3
65
0
Order By: Relevance
“…Unlike mouse SLX4, human SLX4 contains a sequence resembling the Apollo TRF2-binding motif, which drives TRF2 TRFH -dependent permanent recruitment of the SLX4–MUS81–XPF–SLX1 complex to telomeres 4648 . Using the SLX4–SLX1 complex, TRF2 has been proposed to control telomere-length homeostasis by regulating the trimming mechanism, in which very long telomeres are shortened by t-loop excision.…”
Section: The End Protection Problem: Inhibition Of the Ddrmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike mouse SLX4, human SLX4 contains a sequence resembling the Apollo TRF2-binding motif, which drives TRF2 TRFH -dependent permanent recruitment of the SLX4–MUS81–XPF–SLX1 complex to telomeres 4648 . Using the SLX4–SLX1 complex, TRF2 has been proposed to control telomere-length homeostasis by regulating the trimming mechanism, in which very long telomeres are shortened by t-loop excision.…”
Section: The End Protection Problem: Inhibition Of the Ddrmentioning
confidence: 99%
“…50). The basic domain of TRF2 also inhibits resolvase activities at telomeres, thereby promoting telomere replication and stabilizing t loops 48,49 . Rad51 is also recruited to telomeres by BRCA2 during G2, when it has been suggested to play a role in facilitating telomere replication 51 , thus again demonstrating the complex interaction of the HR machinery with telomeres during and after replication.…”
Section: The End Protection Problem: Inhibition Of the Ddrmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ribosylation-mediated control of TRF1 affinity for telomeric DNA may be one possible mechanism where FANCD2 ensures telomere stability. TRF1 also physically blocks the SLX4-nuclease complex from nucleolytically resolving the T-loop [30]. Thus, TRF1 removal from telomeres may promote nucleolytic resolution of telomeric joint molecule intermediates.…”
Section: Fa Proteins In Telomere Maintenancementioning
confidence: 99%
“…Subsequently, crystallographic, cellular and biochemical studies revealed that SLX4 and its associated nucleases is preferentially recruited to long telomeres via direct interaction between a unique HxLxP (x, any amino acid) motif within the t elomere b inding m otif (TBM) of SLX4 and a docking site at the TRF homology (TRFH) domain of TRF2 (Figure 2B) [38, 47]. The SLX4-nuclease complex is required for multiple aspects of telomere maintenance, including negative regulation of telomere length, regulation of telomere recombination, and prevention of telomere replication defects (manifested as fragile telomeres) [30, 38, 47]. The molecular mechanism behind the role of SLX4 in telomere maintenance likely involves the ability of the SLX4-associated nucleases to process and remove alternate DNA structures such as Holliday Junction (HJ) and T-loop.…”
Section: Fa Proteins In Telomere Maintenancementioning
confidence: 99%